Towards economic integration: proceedings (SADCC GaboroneBW, 1992)
The conference focused on ecomomic integration as the key to sustainable development and future prosperity in Southern africa. Examined ways in which the Southern African Development Coordination Conference can promote deeper economic cooperation and integration, on the basis of balance, equity and mutual benefit; providing for cross border investment trade and a freer movement of factors of production - labour and capital - over national borders.
DC